The Influence of Product Quality and Price Perceptions on Purchasing Decisions on Sarimi Products in Waru Sidoarjo - Alfaiq, Zico Yedya; Wardhani, Nuruni Ika (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The development in the business world is very fast, it can be seen by the many kinds of people's needs. This has resulted in the competition of each company vying to win the competition, by bringing in new customers or retaining old customers. One of the needs that continues to grow and innovate today is the food industry. It is a daily need that is always needed by the community. In this modern era, humans tend to choose something practical and instant. a product that is very well known and loved by the Indonesian people, namely instant noodles, especially sarimi. One of the things that people consider in choosing instant noodle products is price perception and product quality because both influence purchasing decisions. Therefore, this study aims to determine the effect of product quality and price perceptions on purchasing decisions for Sarimi products in Waru Sidoarjo. Methods of data collection using a questionnaire and accidental sampling technique. The population in this study were all consumers who bought Sarimi products in Waru Sidoarjo. The sample in this study amounted to 72 respondents and analyzed using Partial Least Square (PLS). The results of this study indicate that product quality has a significant negative effect on purchasing decisions, while price perceptions have a significant positive direction.